Representations of changing weather conditions and outdoor work in the Swedish media: Legitimization of a risk discourse - Bo Nilsson; Jenny Lönnroth (PLoS ONE, 2025)
Accelerating climate change has been associated with, among other things, rising temperatures, rising sea levels, extensive periods of precipitation, and difficult wind conditions. These are said to affect large segments of society, not least outdoor workers, whose working conditions are negatively affected. Much media attention has been paid to the situation of outdoor workers, and the media presents tips on what to consider when working in conditions such as high temperatures. The aim of this paper is to explore how the Swedish media reports on outdoor workers and their working conditions in relation to climate change and difficult weather conditions, especially high temperatures. The aim is also to describe and analyze how an identified risk discourse is legitimized in media representations of extreme weather and outdoor work. The study is based on a qualitative analysis of 72 articles in the Swedish media, available in the digital archive retriever.com (Mediearkivet). A social constructionist perspective is used to explore how weather, climate, and risks are “constructed” in the material, and a focus on storytelling techniques and legitimization strategies makes it possible to investigate how certain views of weather, climate, and risks are justified. According to the results, climate change and changing weather conditions are related to risks at both a structural level and an everyday level in working life. Two overall categories of risk are identified, on one side physiological and mental risks, and on the other economic and technological risks. Together, these categories underpin a general risk discourse that is legitimized using strategies such as scientification, dramatization, and personification. The conclusion is that the media representations are characterized by a de-politization of climate change and changing weather conditions, and by a focus on individual adaptation to these changes.